Impact of witnessing abuse of their mother and childhood trauma on men's perpetration of intimate partner violence in the cross-sectional UN multi-country study on men and violence in Asia and the Pacific - Rachel Jewkes; Ruchira Tabassum Naved; Naeema Abrahams; Nwabisa Shai; Leane Ramsoomar; Bianca Dekel; Andrew Gibbs; Jani Nöthling; Samantha Willan; Esnat Chirwa (SSM - Mental Health)
Trauma exposure and witnessing intimate partner violence (IPV) in childhood are recognised risk factors for IPV. Using the UN Multi-country Study on Men and Violence in Asia and the Pacific dataset, we describe the pathways through which they influence adult IPV perpetration. Methods: In nine sites, from six countries, data were collected in a two-stage, randomly-selected household survey, with one man aged 18–49 years interviewed per house. 8379 interviews were completed with ever partnered men in Bangladesh, Cambodia, China, Indonesia, Papua New Guinea (Bougainville) and Sri Lanka. We present a Structural Equation Model (SEM) to understand paths through which childhood trauma and witnessing IPV impacted perpetration of physical or sexual IPV in adulthood. Results: Among the men, 25.5% had witnessed IPV, 47.0% had perpetrated physical or sexual IPV. Both witnessing IPV and childhood trauma elevated the likelihood of such perpetration. The SEM showed four paths from witnessing IPV and childhood trauma to the latent variable for physical/sexual IPV perpetration. One was direct and three indirect. Paths were mediated by food insecurity, depression, and a latent variable measuring gender inequitable and anti-social masculinities. The masculinity variable indicators were drug use, harmful alcohol use, bullying, gang membership, fighting with other men, having sex with a sex worker and having raped a non-partner. The direct and indirect effects showed both childhood trauma and witnessing maternal IPV to be important, but childhood trauma the more so. Conclusions: Both childhood trauma and witnessing IPV were important in driving IPV perpetration, with independent effects, however, broader childhood trauma exposure was most strongly associated. The effects were mediated by food insecurity, depression and gender inequitable and anti-social masculinities, all recognised risk factors for IPV perpetration. Thus, gender transformative IPV prevention interventions that include mental health and economic elements can mitigate the influence of these key exposures.